2004
DOI: 10.14430/arctic495
|View full text |Cite
|
Sign up to set email alerts
|

Long Foraging Movement of a Denning Tundra Wolf

Abstract: ABSTRACT. Wolves (Canis lupus) on the Canadian barrens are intimately linked to migrating herds of barren-ground caribou (Rangifer tarandus). We deployed a Global Positioning System (GPS) radio collar on an adult female wolf to record her movements in response to changing caribou densities near her den during summer. This wolf and two other females were observed nursing a group of 11 pups. She traveled a minimum of 341 km during a 14-day excursion. The straight-line distance from the den to the farthest locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 22 publications
0
27
0
1
Order By: Relevance
“…This proximity provides breeding wolves with consistent access to caribou following the period when spatial separation between den sites and the main distribution of the herd was the greatest. Previous research on the movement dynamics (timing, direction, and distance) o f Bathurst wolves reported extraterritorial movements away from dens sites only during a 3-week period in late June and early July (Walton et al 2001, Frame et al 2004). …”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…This proximity provides breeding wolves with consistent access to caribou following the period when spatial separation between den sites and the main distribution of the herd was the greatest. Previous research on the movement dynamics (timing, direction, and distance) o f Bathurst wolves reported extraterritorial movements away from dens sites only during a 3-week period in late June and early July (Walton et al 2001, Frame et al 2004). …”
Section: Discussionmentioning
confidence: 96%
“…Pups are bom between mid-May and early-June and remain within close proximity of the den until midSeptember when they are old enough to travel with the pack (Frame et al 2008). Adult wolves generally remain in close proximity to their pups from late-May to early-September (wolf denning period) leaving occasionally to hunt for prey (Williams 1990, Walton et al 2001, Frame et al 2004). As such, the behavior of tundra wolves is likely more territorial during the denning period (Walton et al 2001).…”
Section: Chapter 1: Thesis Introduction Contextmentioning
confidence: 99%
See 3 more Smart Citations